2012
DOI: 10.14221/ajte.2012v37n3.5
|View full text |Cite
|
Sign up to set email alerts
|

School Co-ordinators: Leaders of Learning in Professional Experience

Abstract: It is widely accepted that professional experience or practicum is 'a critically important part of teacher education courses and is consistently valued highly by student

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…Darling-Hammond, 2006;Howe, 2006;Le Cornu, 2012;Reid, 2011b). Indeed it is not uncommon that pre-service teachers report that the professional experience was one of the most valuable components of their education degree.…”
Section: Professional Experience As a Mechanism For Engagement And Momentioning
confidence: 99%
“…Darling-Hammond, 2006;Howe, 2006;Le Cornu, 2012;Reid, 2011b). Indeed it is not uncommon that pre-service teachers report that the professional experience was one of the most valuable components of their education degree.…”
Section: Professional Experience As a Mechanism For Engagement And Momentioning
confidence: 99%
“…Studies conducted in Australia and New Zealand have reported that candidates have more positive experiences in schools in which administrators encourage school-wide responsibility for candidates' learning and their inclusion into the community (Le Cornu, 2012;Ussher, 2010). Varrati et al (2009) interviewed 10 school principals in the United States who indicated their commitment to supporting the practicum but noted they had very limited time.…”
Section: School Administrators' Responses To the Practicummentioning
confidence: 99%
“…Their concerns and actions suggest that in planning the practicum curriculum universities need to consider administrators' contributions beyond placing, meeting, and greeting candidates. Establishing formalized school-university agreements may prompt administrators to develop a greater level of ownership for shaping solutions to the practicum problems identified (Le Cornu, 2012). In the absence of such agreements, problems will more likely be micromanaged with the teacher candidates than with program faculty or will remain unaddressed.…”
Section: Implications For Enhancing the Practicum Component Of Initiamentioning
confidence: 99%
See 1 more Smart Citation
“…Professional experience or the practicum is typically regarded by teachers as one of the most important aspects of their preparation for the classroom (Le Cornu, 2012). Moreover, in recent years, the proportion of time allocated to fieldwork in teacher education programs has increased (Hennissen, Crasborn, Brouwer, Korthagen, & Bergen, 2011).…”
Section: Introductionmentioning
confidence: 99%